Consulting to social entrepreneurship initiatives - using business skills to help solve social problems: ERG: a sustainable approach - Sacadura, João Arriaga e Cunha Cabral de (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics